The Role of Islamic Religious Education in Shaping The Islamic Character of The Younger Generation - Faldo Riski Al hidaya; Abdul Azis Khoiri (STIT Pringsewu, 2026)
This study analyzes the strategic role of Islamic Religious Education (PAI) in overcoming moral degradation among Indonesian youth due to deviant behavior such as violence, bullying, and misuse of digital technology, with an emphasis on Islamic character building based on divine obligations from the Qur'an (At-Tahrim: 6) and the hadith of fitrah, encompassing the pillars of shiddiq, amanah, tabligh, and fathonah. Using a qualitative literature study approach from primary sources (the Qur'an, hadith, classical Islamic texts) and secondary sources (journals), the analysis integrates the concepts of Islamic education al-tarbiyah as the holistic cultivation of human potential (khalaqiyyah, rūhiyyah, 'aqliyyah, akhlāqiyyah) towards perfection; al-ta'lim as the transformation of critical knowledge from birth involving cognitive, affective, and psychomotor aspects; and al-ta'dib as disciplinary education for the habit of noble character to achieve human adabi which collaborate despite different emphases, in order to produce a generation that is faithful, pious, and adaptive in a multicultural society.